The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1080/20786190.2017.1340250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of self-monitoring of blood glucose on glycaemic outcome among type 2 diabetic patients

Abstract: Background: Diabetes mellitus is a chronic metabolic disorder which leads to complications especially when not properly managed. The role of self-monitoring of blood glucose (SMBG) in type 2 diabetic patients using oral hypoglycaemic agents has been a source of controversy. Objective: The objective was to study the effect of SMBG on glycaemic outcome among type 2 diabetics in a primary care setting. Methodology: A randomised control study was conducted between March 2013 and November 2013 at the General Outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Almost half (44%) of the trials investigated SMBG with readings used to adjust therapy. The therapy adjusted was pharmacotherapy—by nurses and physicians—except for two trials where investigators—whose professions were not reported—adjusted this (Barnett et al, 2008; Sodipo et al, 2017), and one trial where therapy adjusted was diet, by dietitians (Suriyawongpaisal et al, 2016). Most trials investigated participants who are not newly diagnosed (diabetes duration of >1 year), except for four (Durán et al, 2010; Kan et al, 2017; O’Kane et al, 2008; Sodipo et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost half (44%) of the trials investigated SMBG with readings used to adjust therapy. The therapy adjusted was pharmacotherapy—by nurses and physicians—except for two trials where investigators—whose professions were not reported—adjusted this (Barnett et al, 2008; Sodipo et al, 2017), and one trial where therapy adjusted was diet, by dietitians (Suriyawongpaisal et al, 2016). Most trials investigated participants who are not newly diagnosed (diabetes duration of >1 year), except for four (Durán et al, 2010; Kan et al, 2017; O’Kane et al, 2008; Sodipo et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The therapy adjusted was pharmacotherapy, by nurses and physicians, except for two trials where investigators, whose professions were not reported, adjusted this (Barnett et al, 2008;Sodipo et al, 2017), and one trial where therapy adjusted was diet, by dietitians (Suriyawongpaisal et al, 2016). Most trials investigated participants who are not newly diagnosed (diabetes duration: > 1 year), except for four (Durán et al, 2010;Kan et al, 2017;O'Kane et al, 2008;Sodipo et al, 2017). <Table 1.> No trials reported only the median or interquartile range, eliminating the need for transformations and estimations of values by formulae respectively (Luo et al, 2018;Wan et al, 2014).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This means that T2DM patients have their blood sugar monitored only when they choose or monthly during clinic appointments. The generally low use of glucometers may also be attributed to factors including cost, doctors not recommending/promoting SMBG, results are not acted upon, and painful needle pricks (Sodipo, Adedokun, & Olusola, ). Therefore, it is important in the SI to recommend SMBG as an important procedure for all the population with diabetes, as it will increase awareness of their daily blood sugar targets, thus facilitating positive/proactive decision making with regard to exercise, diet and medication use in order to better manage their condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, Polonsky and colleagues [13] previously noted statistically significant improvements in both glycaemic control and GV defined by the MAGE in participants with both insulin-treated and non-insulin treated T2D with structured SMBG. Clinical trials and meta-analyses continue to report inconsistent differences in responses associated with participants' glycaemic control when comparing structured and unstructured SMBG [5][6][8][9][13][14]16], thus complicating trial data interpretation. To date, GV is infrequently reported in SMBG trials, which is the purpose of this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to identifying hypoand hyper-glycaemia, SMBG is associated with improved glycaemic control in T1D and insulin-treated T2D [1][2][3]. In people with non-insulin treated T2D the benefits associated with SMBG are less clear, in part because trials employ variable SMBG interventions with different study populations [4][5][6][7][8][9][10][11][12][13][14][15][16]. However, trials using structured SMBG more consistently demonstrate significantly greater improvements in glycaemic control than unstructured SMBG [4,[6][7][9][10][12][13].…”
Section: Introductionmentioning
confidence: 99%